2020
DOI: 10.1101/2020.05.29.123943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interleukin-10 and Small Molecule SHIP1 Allosteric Regulators Trigger Anti-Inflammatory Effects Through SHIP1/STAT3 Complexes

Abstract: 28The anti-inflammatory actions of interleukin-10 (IL10) are thought to be mediated primarily by the STAT3 29 transcription factor, but pro-inflammatory cytokines such as interleukin-6 (IL6) also act through STAT3. 30We now report that IL10, but not IL6 signaling, induces formation of a complex between STAT3 and the 31 inositol polyphosphate-5-phosphatase SHIP1 in macrophages. Both SHIP1 and STAT3 translocate to the 32 nucleus in macrophages. Remarkably, sesquiterpenes of the Pelorol family we previously descr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Recently Mui and co-workers demonstrated that AQX-1125 is ineffective in treating inflammation in IL-10 knockout mice, while more potent SHIP1 agonists are effective in this model. 31 This report also showed that AQX-1125 only binds to SHIP1 weakly, with SHIP1 perhaps not being the primary cellular target of the molecule. These results may explain the lack of activity of AQX-1125 on OPM2 cells.…”
Section: Scheme 4 Analog Synthesismentioning
confidence: 73%
“…Recently Mui and co-workers demonstrated that AQX-1125 is ineffective in treating inflammation in IL-10 knockout mice, while more potent SHIP1 agonists are effective in this model. 31 This report also showed that AQX-1125 only binds to SHIP1 weakly, with SHIP1 perhaps not being the primary cellular target of the molecule. These results may explain the lack of activity of AQX-1125 on OPM2 cells.…”
Section: Scheme 4 Analog Synthesismentioning
confidence: 73%
“…Mui and co-workers have reported the identification of the site on the C2 domain of SHIP1 where PI(3,4)P 2 and SHIP1 agonists bind to accelerate the phosphatase reaction [ 148 ]. The identification of this site should accelerate the development of SHIP1 agonists, which also may exhibit antitumor properties [ 145 ].…”
Section: Comparison Of Crystal Structures Of the Ship1 And Ship2 Pmentioning
confidence: 99%
“…One of the drawbacks of the terpenoid scaffold was the generally poor water solubility of the pelorol analogs. This was addressed by adding basic nitrogens to the scaffold with the synthesis of 16 and 17, which significantly increased water solubility and oral bioavailability [ 148 , 178 , 180 ]. AQX-435 was recently shown to significantly reduce tumor volume in murine models using a panel of mice bearing TMD8 or DLBCL PDX tumors [ 180 ].…”
Section: Ship Agonistsmentioning
confidence: 99%
See 2 more Smart Citations